WOMEN`S TRAUMATIC EXPERIENCES IN TONI MORRISON`S BELOVED - Pioro Benevolent Lariesto; Friston Simalango (LPPM Universitas Katolik Santo Thomas Medan, 2025)
This thesis explores the traumatic experiences of women in Toni Morrison's Beloved. It employs a qualitative narrative research approach as proposed by Creswell, with data collected through a compilation of stories. The theoretical framework is feminism, which is understood as both a social movement and a field of study aimed at elevating women's status within patriarchal societies or environments. The analysis focuses on loss and violence as key factors in the trauma experienced by women subjected to slavery. This study identifies two primary causes of women's trauma: loss, as exemplified by Sethe, who endures severe trauma under slavery, and violence, which she faces at the hands of slave owners and through systemic oppression. The novel reveals how trauma, loss, and violence not only devastate individual lives but also shape collective experiences of suffering and the ongoing struggle for identity and freedom. The study concludes that Toni Morrison illustrates that women's traumatic experiences encompass various dimensions, primarily loss and violence.